1987
DOI: 10.1103/physrevlett.58.487
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport and the coupling of plasma diffusion and heat flow

Abstract: Anomalous transport has been observed in heat-pulse tokamak experiments in the form of faster thermal diffusion than expected from thermal conductivity alone. The anomaly is resolved by correct treatment of time-dependent transport, coupling heat flow and plasma diffusion. The diffusion rates are exhibited as invariant eigenvalues appearing in the transport model. We show how these eigenvalues couple the basic transport processes. The thermal diffusion rate is not determined by thermal conductivity, since it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…(heat pulse) should not be compared to Xe qu (equilibrium), but instead, to an incremental thermal diffusivity, Xe nc -Experimental results from the Joint European Torus (JET) have been reconciled using this formalism. 5 Enhanced transport due to increased magnetic or electrostatic fluctuations during the sawtooth cycle has also been proposed as a potential resolution to the discrepancy between perturbative and equilibrium estimates of Xe- 4 Theoretical treatment of the problem by Hossain et al 6 and Bishop and Connor 7 provides yet another possible explanation for the apparent anomaly by including density effects, when solving the heat equation, and formally treating the coupling of plasma diffusion and heat flow. As a consequence, one might expect to observe a strong spatial and temporal correlation between the sawtooth temperature and density perturbations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(heat pulse) should not be compared to Xe qu (equilibrium), but instead, to an incremental thermal diffusivity, Xe nc -Experimental results from the Joint European Torus (JET) have been reconciled using this formalism. 5 Enhanced transport due to increased magnetic or electrostatic fluctuations during the sawtooth cycle has also been proposed as a potential resolution to the discrepancy between perturbative and equilibrium estimates of Xe- 4 Theoretical treatment of the problem by Hossain et al 6 and Bishop and Connor 7 provides yet another possible explanation for the apparent anomaly by including density effects, when solving the heat equation, and formally treating the coupling of plasma diffusion and heat flow. As a consequence, one might expect to observe a strong spatial and temporal correlation between the sawtooth temperature and density perturbations.…”
mentioning
confidence: 99%
“…These results provide experimental support for the theoretically predicted coupling of plasma diffusion and heat flow. 6,7 Measurements of the sawtooth density perturbation are made with a multichannel interferometer system possessing high spatial (Ax -1.5 cm) and high phase (An e < 5*\0 ]0 cm -3 ) resolution. 8 An Abel inversion is performed to arrive at the local sawtooth density perturbation profile.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Fredrickson et al 1 suggested that either an anomalously high value of Xe, due perhaps to fluctuations, or an inward heat pinch could explain the differences in the Xe obtained. Hossain et al 8 found that the different values of Xe could be explained on the basis of coupled heat flow and plasma diffusion, but they could not rule out enhanced transport due to magnetic or electrostatic fluctuations. If turbulent transport is driven by temperature or density gradients (as predicted by many theories), the passage of a heat or density pulse would cause the resulting transport coefficients to be significantly different from their equilibrium values.…”
mentioning
confidence: 99%
“…The picture described above is completely analogous to the heat-pulse counterpart and suggests a coupling between the two phenomena. 7,8 An Abel inversion is performed to arrive at the local sawtooth density-perturbation profile. In order to minimize errors near the crash where m = 1 oscillations are often large, a numerical boxcar averaging technique is applied during the plateau region of the discharge where the sawtooth period and amplitude are essentially constant.…”
mentioning
confidence: 99%